Development of Digital-Based Job Training Methods at the Regional Library and Archives Service of West Java Province - Ika Hasillah; Lia Muliawaty; Taqwaty Firdausijah (Journal Of Data Science, 2026)
Digital transformation in the library sector demands increased human resource competency to provide effective, efficient, and adaptive public services to technological developments. However, the on-the-job training methods implemented at the West Java Provincial Library and Archives Service are still dominated by conventional approaches, thus not fully supporting the development of employee digital competencies. This study aims to analyze and develop a digital-based on-the-job training model that aligns with organizational needs and the demands of modern library services. The study employed a qualitative approach with descriptive methods. Data were collected through observation, literature review, and in-depth interviews with informants. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that developing a digital-based on-the-job training method requires integrating on-the-job and off-the-job training methods with the use of digital technology through a Learning Management System (LMS), virtual service simulations, knowledge sharing, role-playing, simulations, professional forums, and strengthening cross-divisional coordination. The developed model can improve employee technical and managerial competencies, strengthen adaptability to digital transformation, and support improvements in the quality of library and archives services. This research also yielded three novelties: the Digital Competency Integration Method, the Workload-Based Local E-Learning Module Method, and the Train-of-Trainer (ToT) Method as a model for continuous competency development. These three methods are expected to enhance the professionalism of civil servants, accelerate digital transformation, and achieve excellent service at the West Java Provincial Library and Archives Service.